Application of additive manufacturing for the adaptive design of ultrasound phantoms - Zalka, Lukas; Köhrer, Johannes; Songsaeng, Chatsuda; Homolka, Peter; Kollmann, Christian; Hummel, Johann; Figl, Michael (Frontiers in Physics, 2025)
IntroductionThe image formation process of conventional pulse-echo Ultrasound mainly uses the backscattered amplitude and assumes constant attenuation and speed of sound in the penetrated media. Thus, many commercially available ultrasound imaging phantoms use only a limited choice of materials with simple geometric shapes. Part of today’s research in ultrasound is to gain more information on the acoustic properties of the object imaged. These advanced imaging and reconstruction procedures require more complicated phantom designs that contain different materials with precisely designable acoustic properties for validation and quality assurance (QA).MethodsTo fabricate such phantoms, we produced molds for casting ultrasound phantoms using additive manufacturing. Phantom materials used were based on agar and polyvinyl alcohol. To adapt the speed of sound glycerol was added to the mixtures. As glycerol diffuses out of the phantom material, polluting the surrounding water, we designed a watertight sample holder. The effect of the freeze-thaw cycles (FTCs) on the acoustic properties of the polyvinyl alcohol (PVA)-based phantoms was also investigated. Speed of sound and attenuation were determined for both phantoms materials, and Shore hardness measured for the PVA-based phantoms.ResultsShore hardness of the PVA phantoms increased by up to 79% of the initial value with increasing number of freeze-thaw cycles, but showed a saturation after 5 FTCs. However, the number of FTCs had only a small effect on the speed of sound and attenuation, as the sound speed increased slightly from 1,530.14 m/s to 1,558.53 m/s, (1.86%) and the attenuation exhibited only an increase of 6.75%. In contrast, differences of around 100 m/s in the speed of sound in the PVA phantoms (from 1,558.53 to 1,662.27 m/s), as well as in the agar-based phantoms (from 1,501.74 to 1,609.36 m/s) could be achieved by adding glycerol, making these materials appropriate candidates for the design and fabrication of US phantoms with defined sections and details with different speed of sound and attenuation. The use of the sample holder showed only an influence of 0.63% on the measured speed of sound.Discussion3D printed molds led to an improved manufacturing process as well as a free choice of the shape of the phantoms. A sample holder could prevent contamination of the water with no significant differences in the measured speed of sound.